Analysis on Effects of Corrosion Length, Width and Depth on Stress State of Large - Area Corrosion Defects Pipes - ZHOU Li - jian, CAO Wu - peng, LU Zhao - hong, WEI Li - xin, ZHU Dong - lin, YAN Feng (Cailiao Baohu)
Aiming at the problem of pipeline damage caused by large - area flaky corrosion defects, ABAQUS software and actual data were used to establish corroded pipeline models under different corrosion conditions, and the orthogonal test method was used to analyze the stress state. The simulation results were compared with the API579 standard results to verify the accuracy. Results showed that the corrosion length, width and depth all had effects on the stress state of pipelines with large - area corrosion defects, of which the corrosion depth had the most significant influence and the corrosion length had the least influence; the corrosion width also had a greater influence on the pipeline stress state within a certain range of 40°～80°. When the corrosion width was over 80°, the stress change tended to be stable. Besides, different corrosion size parameters had different effects on the stress state of the pipeline, among then the corrosion depth had the greatest influence. Consequently, the impact of corrosion depth must be focused on when carrying out pipeline reinforcement, remaining life estimation and safety assessment.